Discovery of SYD5115, a novel orally active small molecule TSH-R antagonist. (15th April 2023) - Karstens, Willem F.J.; M.B.P. Menge, Wiro; Martens, Gijs; op het Veld, Sanne J.N.; Th.H. van Eupen, Jacobus; Demon, Marco; van Achterberg, Tanja A.E.; Arisse-Thijssen, Monica J.; Santegoeds-Lenssen, Ellen W.H.; van der Lee, Miranda M.C.; Ubink, Ruud; Arends, Roel J.; et al.
Graphical abstract: Highlights: Discovery of a novel class of thyrotropin receptor antagonists. A highly potent compound with oral efficacy was identified. Risk of mutagenicity of compounds strongly reduced. Efficacy correlates with exposure after oral dosing. Abstract: The thyrotropin receptor (TSH-R) regulates the thyroid gland and is normally activated by thyrotropin. In patients with Graves' disease, TSH-R is also stimulated by stimulatory TSH-R autoantibodies leading to hyperthyroidism. In this paper, we describe the discovery of SYD5115 (67 ), a novel small molecule TSH-R antagonist with nanomolar potency. SYD5115 also blocks stimulating antibody induced synthesis of the thyroid hormone thyroxine (T4 ) in vivo, after a single oral dose. During optimization, several issues had to be addressed such as the low metabolic stability and the potential mutagenicity of our first series of compounds.